(untitled) (International Journal of Applied Sciences and Biotechnology, 2014)
The seed materials were received from National Wheat Research Program, Bhairahawa and field experiment was conducted at Regional Agricultural Research Station Tarahara during 2012 and 2013 in wheat growing season. The topography of the experimental site was 130 masl with sandy loam soil. The trial included 24 wheat genotypes laid out in alpha lattice design in eight sub blocks within two main blocks. The eastern region of Nepal has been facing the problem of sterility caused by different stresses during reproductive growth stage. So we need to develop the early maturing variety with high yielding potential that could escape the reproductive damage from rainfall, hot westerly wind and leaf rust epidemic. In this study, we identified BL3594, NL1026, NL297, BL3978 and NL1140 as early maturing wheat genotypes with 102, 102, 101, 97 and 102 days of maturity, respectively. The genotypes varied significantly for heading days, maturity days, plant height, spikes per meter square, grain per spikes and grain yield ton per hector. The most stable yield producing genotypes were BL3264, BL3535, BL3623, NL1135 and BL3978. The variety BL3978 had maturity duration of 97 days, even earlier than check variety NL297. The genotypes NL1093 and NL1094 had highest grain per spikes although had negative correlation coefficient with panicle length consequently led to the lower yield. The new genotypes like BL3978, BL3594 and NL1140 should be promote as appropriate varieties for terai region of Nepal. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11625 Int J Appl Sci Biotechnol, Vol. 2(4): 574-578